Urinary Bladder Injury Among Patients with Placenta Accreta Spectrum: Comparison Between Wedge Resection and Total Hysterectomy - Ismayadi, Tedi; Pribadi, Adhi; Kurniadi, Andi (Indonesian Journal of Obstetrics & Gynecology Science, 2025)
Objective: This study aims to assess the incidence of urinary bladder injury among pregnant women with placenta accreta spectrum (PAS) who underwent total hysterectomy and wedge resection.Methods: This study employed a cross-sectional design by reviewing secondary data of all pregnant women with PAS who underwent total hysterectomy or wedge resection at Hasan Sadikin General Hospital from January 2021 to December 2023. Statistical analysis for categorical data used the Chi-square test or Fisher’s exact test, and numerical data were analyzed using the unpaired T-test or Mann-Whitney test.Results: The sample consists of 116 patients. A total of 84 patients underwent total hysterectomy, and 32 patients underwent wedge resection. There was no significant difference in mean age between the two groups (p = 0.129). The results showed a significant difference between the two groups for birth weight (p = 0.007) and the incidence of urinary bladder injury (p = 0.018). No urinary bladder injury occurred in the wedge resection group, while 13 (15.50%) patients experienced urinary bladder injury in the total hysterectomy group.Conclusion: Total hysterectomy is associated with a higher incidence of urinary bladder injury compared to wedge resection.Cedera Vesika Urinaria pada Pasien dengan Spektrum Plasenta Akreta:Perbandingan antara Wedge Resection dan Total HisterektomiAbstrak Tujuan: Penelitian ini bertujuan untuk menilai angka kejadian cedera vesika urinaria antara wanita hamil dengan spektrum plasenta akreta (SPA) yang menjalani histerektomi totalis dan wedge resection.Metode: Metode yang digunakan dalam penelitian ini adalah metode potong lintang dengan meninjau data sekunder semua ibu hamil dengan SPA yang menjalani histerektomi totalis atau wedge resection di Rumah Sakit Umum Pusat Hasan Sadikin periode Januari 2021 - Desember 2023. Analisis statistik untuk data kategorik menggunakan uji Chi-square atau uji Fisher dan data numerik diuji menggunakan uji T-tidak berpasangan atau uji Mann-Whitney.Hasil: Sampel penelitian ini terdiri atas 116 pasien. Sebanyak 84 pasien menjalani histerektomi totalis dan 32 pasien menjalani wedge resection. Tidak ada perbedaan rata-rata usia yang bermakna antar kedua kelompok (p = 0,129). Hasil penelitian menunjukkan perbedaan yang signifikan antara kedua kelompok untuk berat badan lahir (p = 0,007) dan kejadian cedera vesika urinaria (p = 0,018). Tidak ada yang mengalami cedera vesika urinaria pada kelompok wedge resection, sedangkan 13 (15,50%) pasien mengalami cedera vesika urinaria pada kelompok histerektomi totalis.Kesimpulan: Histerektomi totalis berhubungan dengan tingkat kejadian cedera vesika urinaria yang lebih tinggi dibandingkan dengan wedge resection.